Effect of LED photobiomodulation on dental implant osseointegration: An in vivo study - Jean-Marc Foletti; Floriane Remy; Luc Chevenement; Manon Sterba; Patrick Tavitian; Laurent Badih; Olivia Kenck-Veran (Tabriz University of Medical Sciences, 2023)
Background. Photobiomodulation (PBM) may be prescribed after dental surgery to accelerate tissue healing and improve implant stability. The objective of this study is to evaluate the efficiency of LED-PBM on the dental implant osseointegration. Methods. A total of 48 implants (KontactTM) were inserted in 8 Yucatan minipigs (6 implants per minipig) divided into 2 groups (test and control). The test group received LED-PBM with a total energy of 124.2 J/cm2 delivered over 4 sessions (at day0, day+8, day+15 and day+28) lasting 12 minutes each. At day+28, all animals were sacrificed, and their mandibles removed to perform histologic and histomorphometric analysis. Implant osseointegration was evaluated using the computation of bone/implant contact (BIC) index and bone surface/total surface (BS/ TS) ratio. The groups were compared using Student's unpaired t test. Results. BIC index and BS/TS ratio were significantly higher within the test group as compared to the control group (P<0.01). Histologic observations on bone tissues demonstrated that LED-PBM may improve and accelerate dental implant osseointegration: 25% of dental implants analyzed within the test group were completely osseointegrated, versus 12.5% within the control group. Conclusion. This experimental study indicates that LED-PBM contributes to enhancing implant treatment outcomes.